Use of ultra-wide field retinal imaging and optical coherence tomography angiography in the diagnosis of incomplete Susac syndrome. - Alba-Linero, Carmen; Liscombe-Sepulveda, John Paul; Llorenç, Víctor; GiraltJosa, Joan; Adán, Alfredo (Sage, 2020)
El artículo se centra en el diagnóstico de la Síndrome de Susac (Susac syndrome) incompleto mediante técnicas avanzadas de imagen: imágenes de campo ultra amplio (ultra wide field, UWF) de la retina y angio tomografía de coherencia óptica (OCT A).

Purpose:To describe clinical findings through ultra-wide field (UWF) images and optical coherence tomography angiography (OCT-A), in Susac’s syndrome (SS). Methods:SS patients were retrospectively analyzed in a single center. Clinical features, ultra-wide-field retinographies (UWF-PR), UWF fluorescein angiographies (UWF-FA), and optical coherence tomography angiography & en face (OCT-A/EF) were reviewed. Results:Twelve eyes from six patients with a mean follow-up of 35.66 months ± SD 36.88 were included. UWF-PR showed areas of retinal whitening and cotton-wool spots in all the eyes after acute attack. Segmentary mid peripheral arteriolitis could be observed in five eyes by UWF-FA in acute and convalescent stages. OCT-A revealed capillary density changes in all of the affected eyes. During the acute phase there was a well-preserved superficial capillary network, while deep retinal plexus showed a lower density in the affected areas. OCT-A/EF revealed deep retinal plexus drop-out and surrounding edematous retina in acute attacks, becoming atrophic over time. Conversely, superficial plexus was much less affected. Perifoveal reperfusion was seen in seven eyes after the acute attack. Conclusions:UWF-PR/FA and OCT-A/EF might be helpful to stablish an early diagnosis and to monitor SS progression.
https://openpolicyfinder.jisc.ac.uk/id/publication/11477
Keywords: Ojos - Inflamación; Uveítis; Inmunología; Sistema cardiovascular - Enfermedades; Arterial occlusive disease; Susac’s syndrome; Choroidal/retinal inflammation; Immunology; Posterior uveitis; Techniques of retinal examination; Uveitis